Liberia, South Carolina : an African American Appalachian community - Coggeshall, John M. (University of North Carolina Press, 2018)
"In 2007, while researching mountain culture in upstate South Carolina, anthropologist John M. Coggeshall stumbled upon the small community of Liberia, in the Blue Ridge foothills. There he met Mable Owens Clarke and her family, the remaining members of a small African American community still living on land obtained immediately after the Civil War. This intimate history tells the story of five generations of the Clarke family and their friends and neighbors, chronicling their struggles through slavery, Reconstruction, the Jim Crow era, and the desegregation of the state. Through hours of interviews with Mable and her relatives, as well as friends and neighbors, Coggeshall presents an ethnographic history that allows a largely ignored community to speak and record their own history for the first time"--